2015
DOI: 10.1037/fam0000043
|View full text |Cite
|
Sign up to set email alerts
|

Mediation and moderation of divorce effects on children’s behavior problems.

Abstract: Using data from the NICHD Study of Early Child Care and Youth Development, we examined children’s internalizing and externalizing behavior problems from age 5 to age 15 in relation to whether they had experienced a parental divorce. Children from divorced families had more behavior problems compared with a propensity score-matched sample of children from intact families according to both teachers and mothers. They exhibited more internalizing and externalizing problems at the first assessment after the parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
1
25

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 50 publications
1
77
1
25
Order By: Relevance
“…Havermans, Botterman, and Matthijs () found that the effects of divorce on school engagement were partially mediated by the quality of mother–child and father–child relationships, as well as parental conflict. Finally, in Weaver and Schofield (), the effects of divorce on teacher‐reported internalizing behaviors were mediated by the postdivorce income‐to‐needs ratio, whereas mother‐reported internalizing behaviors were mediated by the income‐to‐needs ratio, the quality of the home environment, and maternal depression. The quality of the home environment and maternal depression mediated the link between divorce and teacher‐reported externalizing behaviors, whereas the quality of the home environment and the income‐to‐needs ratio mediated the effects for mother‐reported externalizing behaviors.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Havermans, Botterman, and Matthijs () found that the effects of divorce on school engagement were partially mediated by the quality of mother–child and father–child relationships, as well as parental conflict. Finally, in Weaver and Schofield (), the effects of divorce on teacher‐reported internalizing behaviors were mediated by the postdivorce income‐to‐needs ratio, whereas mother‐reported internalizing behaviors were mediated by the income‐to‐needs ratio, the quality of the home environment, and maternal depression. The quality of the home environment and maternal depression mediated the link between divorce and teacher‐reported externalizing behaviors, whereas the quality of the home environment and the income‐to‐needs ratio mediated the effects for mother‐reported externalizing behaviors.…”
Section: Resultsmentioning
confidence: 94%
“…A further four that presented X → M, M → Y, and X → Y data found evidence of partial mediation by at least one type of transition and stressor (Havermans et al, ; Lacey et al, , ; Vargas et al, ). Among the studies with behavioral or emotional outcomes, 10 found evidence for full mediation by at least one type of transition and stressor (Averdijk et al, ; Coley et al, ; Fomby, ; Fomby & Osborne, ; Osborne & McLanahan, ; Waldfogel et al, ; Weaver & Schofield, ; Wickrama et al, ; Wu, Hou, & Schimmele, ; Wu & Chiang, ). A further two that presented X → M, M → Y, and X → Y data found evidence of partial mediation by at least one type of transition and stressor (Bachman et al, ; Vargas et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Co‐parenting an infant or very young child after separation involves complex developmental considerations, and disputes over the best way to go about this are common in family law. Vulnerabilities of infants and toddlers to chronic and acute disruptions in parenting responsiveness before and after separation are well documented (Lucas, Nicholson, & Erbas, ; Weaver & Schofield, ). Agreement is widespread on the potentially enduring consequences for young children and with this the need to ensure “that essential components of early development are not jeopardized by the post separation parenting arrangement” (Pruett, McIntosh, & Kelly, , p. 241).…”
Section: Introductionmentioning
confidence: 99%
“…Literature on divorce and separation suggests that this has a considerable impact on the wellbeing of children and young people and can result in longterm poor outcomes (Bream and Buchanan, 2003). Behavioural problems and performing less well in school are just two of the resultant outcomes usually experienced (Weaver et al, 2015). Whilst severe distress is usually short-term at the time of separation, it is often increased again when adjusting to new reconstituted family dynamics.…”
Section: Separation and Reconstituted Familiesmentioning
confidence: 99%